Efektivitas Implementasi Penguatan Sektor Pariwisata dan UMKM Kabupaten Ponorogo di Masa Pandemi Covid-19 - Galih Ajeng Ullifah; Nurul Azizah Freya Fidela; Wahyu Ikke Siswika Lestari; Dian Suluh Kusuma Dewi (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2024)
Ponorogo is one of the many areas that have also been seriously affected by the COVID-19 outbreak. The governance of tourism and UMKM will have an impact on the environment that is controlled by the local government, which is why the development of the tourism sector and UMKM’s, especially in the Ponorogo area, is very important in order to improve the welfare of the community and the regional economy. UMKM actors have also experienced a decline in income due to the Covid-19 pandemic. By strengthening the role of local governments as the leading tourism sector and regional UMKM’s are considered to be able to encourage collaboration between sectors to manage local tourism and sustainable UMKM’s. This paper was written with the aim of finding out how far the role of local government is and how the relationship between sectors (actors) in managing local tourism and UMKM’s. In tourism management, the role is not only carried out by one party but all the supporting aspects involved in creating orchestration and ensuring quality of activities, facilities, services, to create experiences and value benefits of tourism so as to provide benefits and benefits to the community and the environment.